PELAYANAN SPT TAHUNAN BERDASARKAN PRINSIP SIPAKAINGE - Syarifuddin, Safria; Sari, Sri Nirmala; Ilham, Ilham; Arifin, Rukminih; Den Ka, Veronika Sari (Institut Teknologi dan Bisnis Swadharma, 2024)
The Indonesian Directorate General of Taxation, through the Regional Office for South, West, and Southeast Sulawesi, has a collaboration program with the Bosowa Polytechnic in terms of community service by establishing the Bosowa Polytechnic Tax Center with Tax Volunteer Program, which is carried out every year. Tax volunteers are a community service program for students from various universities to help taxpayers and help the tax office carry out the annual tax reporting program. Through tax volunteer activities, students are able to increase literacy in the field of taxation, especially for students of the D3 Taxation Study Program at the Bosowa Polytechnic who receive placement locations in Makassar City. Lecturers and students carry out community service by helping individual and corporate taxpayers fill out their annual tax returns.Â Direktorat Jenderal Pajak RI, melalui Kantor Wilayah Sulawesi Selatan, Barat, dan Tenggara, memiliki program kerja sama dengan Politeknik Bosowa dalam hal pengabdian kepada masyarakat dengan membentuk Tax Center Politeknik Bosowa dengan Program Relawan Pajak yang dilaksanakan setiap tahun. Relawan pajak merupakan program pengabdian masyarakat bagi mahasiswa dari berbagai perguruan tinggi untuk membantu wajib pajak dan membantu kantor pajak dalam melaksanakan program pelaporan pajak tahunan. Melalui kegiatan relawan pajak, mahasiswa mampu meningkatkan literasi di bidang perpajakan khususnya bagi mahasiswa Program Studi D3 Perpajakan Politeknik Bosowa yang mendapat lokasi penempatan di Kota Makassar. Dosen dan mahasiswa melakukan pengabdian kepada masyarakat dengan membantu wajib pajak orang pribadi dan badan dalam mengisi SPT tahunan.